2015
DOI: 10.1007/s11420-015-9458-4
|View full text |Cite
|
Sign up to set email alerts
|

Young Females Exhibit Decreased Coronal Plane Postural Stability Compared to Young Males

Abstract: Background: Female athletes are at significantly higher risk of noncontact ACL injury than males, particularly in pivoting sports such as soccer and basketball. Sex-based differences in proprioception and core stability may contribute to this elevated risk. Questions/Purpose: This study evaluates a novel method of assessing dynamic stability to test the hypothesis that healthy adolescent controls have sex-based differences in postural stability. Methods: Seventy-nine male and 72 female subjects completed three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(44 reference statements)
0
12
0
1
Order By: Relevance
“…23,46 Previous research into the cause and rate of anterior cruciate ligament injuries in men versus women has shown different biomechanics as well as functional differences in task performance. 6,17,25,32,38 Similar mechanisms may be present in the hip to account for differences in injury rates. For example, prior studies have suggested that anatomic differences in female hips, such as a lower prevalence of cam-type deformities, may help protect against some types of hip injuries.…”
Section: Discussionmentioning
confidence: 99%
“…23,46 Previous research into the cause and rate of anterior cruciate ligament injuries in men versus women has shown different biomechanics as well as functional differences in task performance. 6,17,25,32,38 Similar mechanisms may be present in the hip to account for differences in injury rates. For example, prior studies have suggested that anatomic differences in female hips, such as a lower prevalence of cam-type deformities, may help protect against some types of hip injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The results serve to extend the findings of previous investigations on dynamic balance which have focused on athletes from specific sports, 6,20 older age groups, [40][41][42] or competitive sport. 22,43 The literature indicates that dynamic balance scoring can vary greatly, and can be influenced by a host of factors including testing methodologies, 26,38 the precision of the value reported, 40,[44][45][46][47][48] and the study population's age, [40][41][42] sex, 6,20,46,48,49 sport, 6,20 and competitive level. 22,43,50 YBT scoring for our healthy adolescent female population fell within the range of expected scores based on participants age, gender and competitive level -scores were slightly higher than those previously reported for adults; 26,27,38 slightly lower than adolescent athlete scoring reported for both sexes; 43,51 and most similar to scoring from older female participants.…”
Section: Discussionmentioning
confidence: 99%
“…41,43 Benzer şekilde sağlıklı adolesanlarda yapılan bir çalışmada, koronal planda kadın-ların erkeklere göre daha düşük dinamik stabiliteye sahip olduğu gösterilmiştir. 44 Bunun aksine, Greve ve ark.nın çalışmasında, kadınların erkeklere göre daha iyi denge becerileri sergiledikleri gösterilmiş-tir. Bunun nedeni olarak, erkeklerin BKİ değerle-rinin kadınlara göre daha yüksek olmasının dengeyi olumsuz olarak etkilediği ifade edilmiş-tir.…”
Section: Discussionunclassified